Influence of Social Media Experience on Students' Buying Behavior - SALERA, JOSE PASCO; Bautista, Jade Anberth; Ahiakwo, Kingsley; Regodon, Erica Louie; Mahipit, Noena; Tayaben, Precious; Balila, Jolly; Macalalad, Marta; Perdido, Ron Ivan; SAUSA, LUALHATI (11th International Scholars Conference, 2024)
Each consumer purchase is unique due to varying buying behaviors and influences. Studies reflect changes in society, economics, and technology, which impact consumer behavior. A systematic analysis of knowledge in this area is crucial for future growth. Hence, the study is driven to investigate whether social media marketing experience positively influences students’ buying behavior. Data from 354 randomly selected college students enrolled in a faith-based institution were analyzed. Results proved that social media marketing experiences positively influence students’ buying behavior. It re-affirmed the validity of the stated theories that social media marketing is a tool which shape the behavior of the subject. Results also showed that majority of the students received a positive experience in social media marketing. It implied that social media platforms are one of the best way for businesses to use as a medium for reaching out their target customers in the context of students. Thus, it was recommended to include the kind of product and platform, as social media marketing experience and student buying behavior can change depending on the application the user is engaged on or depending on the kind of product advertised in the platform. By doing so, future studies can identify the specific behavior or experience of customers.